The rise of right-wing populist Pim Fortuyn in the Netherland: A discursive opportunity approach - Ruud Koopmans; Jasper Muis (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2008)
The question addressed in this paper is how to explain the dramatic rise of Pim Fortuyn's right-wing populist party during the campaign for the parliamentary elections in the Netherlands in 2002. Fortuyn succeeded in attracting by far the most media attention of all political actors and his new party won 17 percent of the votes. We analyze how this new populist party managed to mobilize such an amount of attention and support so suddenly and so rapidly. We use the notion of “discursive opportunities” and argue that the public reactions to Pim Fortuyn and his party played a decisive role for his ability to further diffuse his claims in the public sphere and to achieve support among the Dutch electorate. The predictions of the effects of discursive opportunities are empirically investigated with longitudinal data from newspapers and opinion polls. To study these dynamics of the competition over voters' support and over space in the public debate during the election campaign, we use an ARIMA time-series model as well as a negative binomial event count model with lagged variables to account for the time-series structure of the data. We find that discursive opportunities have significantly affected the degree to which Fortuyn was successful in the competition for both voter support, and media attention. Public visibility, resonance and legitimacy in the media significantly affected the opinion polls and higher degrees of legitimacy and negative claims on the issue of immigration and integration in the media by others increased the opportunities for Fortuyn to further diffuse his viewpoints and to become the main political opinion-maker during the turbulent election campaign of 2002. – – Das vorliegende Papier geht der Frage nach, wie sich der dramatische Aufschwung der rechtspopulistischen Partei Pim Fortuyns während des Wahlkampfs zu den niederländischen Parlamentswahlen 2002 erklären lässt. Pim Fortuyn gelang es, verglichen mit den anderen politischen Akteuren die weitaus größte Aufmerksamkeit der Medien auf sich zu lenken, und seine Partei gewann auf Anhieb 17 Prozent der Stimmen. Die Autoren untersuchen, wie es dieser neuen populistischen Partei gelingen konnte, so plötzlich und schnell ein solches Maß an Aufmerksamkeit und Unterstützung zu mobilisieren. Unter Verwendung des Begriffes ,,diskursiver Gelegenheiten“ wird argumentiert, dass die öffentlichen Reaktionen auf Pim Fortuyn und seine Partei entscheidend dazu beitrugen, dass er seine Forderungen in der Öffentlichkeit weiter verbreiten und Unterstützung unter den niederländischen Wählern finden konnte. Die vorhergesagten Effekte der diskursiven Gelegenheiten werden empirisch mit Längsschnittdaten aus Zeitungen und Meinungsumfragen untersucht. Die Analyse der Dynamik des Wettbewerbs um die Gunst der Wähler und um öffentliche Aufmerksamkeit in den Debatten erfolgt mittels eines ARIMA Zeitreihenmodells und eines negativen binomialen event count Modells mit zeitversetzten Variablen, um die Zeitreihenstruktur der Daten angemessen zu berücksichtigen. Die Autoren stellen fest, dass der Erfolg von Fortuyn im Wettbewerb um sowohl Wählerunterstützung als auch Medienaufmerksamkeit signifikant von diskursiven Gelegenheiten beeinflusst wird. Öffentliche Sichtbarkeit, Resonanz und Legitimität in den Medien übten einen signifikanten Einfluss auf die Meinungsumfragen aus. Ein höheres Maß an Legitimität und eine größere Zahl von negativen Forderungen zum Thema Immigration und Integration, die von anderen in die Medien getragen wurden, erhöhten für Fortuyn die Gelegenheiten, seine Ansichten zu verbreiten und im Verlaufe des turbulenten Wahlkampfs 2002 zum wichtigsten politischen Meinungsmacher aufzusteigen.
Keywords: 300